Engineering and malaria control: learning from the past 100 years - Konradsen, Flemming; Hoek, Wim van der; Amerasinghe, Felix P.; Mutero, Clifford M.; Boelee, Eline (2004)
Traditionally, engineering and environment-based interventions have contributed to the prevention of malaria in Asia. However, with the introduction ofDDTand other potent insecticides, chemical control became the dominating strategy. The renewed interest in environmental-management-based approaches for the control of malaria vectors follows the rapid development of resistance by mosquitoes to the widely used insecticides, the increasing cost of developing new chemicals, logistical constraints involved in the implementation of residual-spraying programs and the environmental concerns linked to the use of persistent organic pollutants. To guide future research and operational agendas focusing on environmental-control interventions, it is necessary to learn from the successes and failures from the time before the introduction of insecticides. The objective of this paper is to describe the experiences gained in Asia with early vector control interventions focusing on cases from the former Indian Punjab, Malaysia and Sri Lanka. The paper deals primarily with the agricultural engineering and land and water management vector control interventions implemented in the period 1900-1950. The selected cases are discussed in the wider context of environment-based approaches for the control of malaria vectors, including current relevance. Clearly, some of the interventions piloted and implemented early in the last century still have relevance today but generally in a very site-specific manner and in combination with other preventive and curative activities. Some of the approaches followed earlier on to support implementation would not be acceptable or feasible today, from a social or environmental point of view.